Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1128/aem.65.11.4995-5002.1999
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Adhesion at Synthetic Surfaces

Abstract: A systematic investigation into the effect of surface chemistry on bacterial adhesion was carried out. In particular, a number of physicochemical factors important in defining the surface at the molecular level were assessed for their effect on the adhesion ofListeria monocytogenes, Salmonella typhimurium,Staphylococcus aureus, and Escherichia coli. The primary experiments involved the grafting of groups varying in hydrophilicity, hydrophobicity, chain length, and chemical functionality onto glass substrates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(150 citation statements)
references
References 38 publications
(32 reference statements)
8
138
0
2
Order By: Relevance
“…On the other hand, for inhibition via displacement, receptor affinity of the adhesins is also important aside from overall adhesion, such as the way beta-linked galactose is essential for recognition by the E. coli K88ac adhesin (Grange et al 1998). Cunliffe et al (1999) also showed that S. Typhimurium may use a different mode of cell attachment compared to E. coli. In their study, hydropathy did not have an effect on S. Typhimurium attachment, suggesting the presence of adhesion-promoting substances that allows binding to both hydrophobic and hydrophilic substrates.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for inhibition via displacement, receptor affinity of the adhesins is also important aside from overall adhesion, such as the way beta-linked galactose is essential for recognition by the E. coli K88ac adhesin (Grange et al 1998). Cunliffe et al (1999) also showed that S. Typhimurium may use a different mode of cell attachment compared to E. coli. In their study, hydropathy did not have an effect on S. Typhimurium attachment, suggesting the presence of adhesion-promoting substances that allows binding to both hydrophobic and hydrophilic substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery rates can vary from 0.1% to 25% (Moore and Griffith, 2007) and will depend on the technique used but an optimum recovery rate of 10% for Dacron swabs is not uncommon. The type and number of microorganisms sampled can have a major effect on recovery (Rose et al, 2011;Downey et al, 2012) and they can become increasingly difficult to remove once they have adhered to a surface (Cunliffe et al, 1999), particularly in biofilms. Additionally, organism retention within the bud fibers results in poor repeatability and sensitivity.…”
Section: Indirect Methods: Swabbing/sponges/wipesmentioning
confidence: 99%
“…Solutions. Yeast-dextrose broth contained (per L of deionized water) 10 g of peptone, 8 g of beef extract, 5 g of NaCl, 5 g of glucose, and 3 g of yeast extract (10). Phosphate-buffered saline (PBS) contained (per L of deionized water) 8.2 g of NaCl and 1.2 g of NaH 2 PO 4 ‚H 2 O.…”
Section: Methodsmentioning
confidence: 99%